Fabrication and characterization of quantum dot sensitized solar cells with methylcellulose–polysulphide gel polymer electrolyte / Muhammad Ammar Mingsukang - Muhammad Ammar , Mingsukang (2019)
Polysulphide liquid electrolyte (PLE) is used as a medium to transport charge from counter electrode (CE) to the photoanode in a quantum dot sensitized solar cell (QDSSC). In this work, novel polysulphide gel polymer electrolyte (PGPE) has been used to replace PLE in order to overcome the problems that result from the use of liquid electrolytes. Methylcellulose (MC) has been chosen as the host polymer since it is biocompatible, cheap, and easily dissolves in water. MC–PGPE with composition of 3.54 wt.% MC, 88.46 wt.% distilled water, 7.78 wt.% Na₂S and 0.22 wt.% S shows the highest room temperature (RT) ionic conductivity of (0.191 ± 0.001) S cm-1 and lowest activation energy of (55.25 ± 1.15) meV. CdS quantum dot (QD) has been used as sensitizer and is deposited on TiO2 semiconducting film using successive ionic layer absorption and reaction (SILAR) method. The [FTO / TiO2 blocking layer / TiO2 mesoporous layer / CdS] assembly is called the photoanode. QDSSC fabricated with the optimized MC–PGPE, optimized photoanode with 5 SILAR cycles for CdS deposition and platinum (Pt) CE i.e. [FTO / TiO2 / CdS(5) / electrolyte / Pt(CE) / FTO] QDSSC assembly shows the best performance with power conversion efficiency (PCE) of (0.77 ± 0.01)%, short circuit current density (Jsc) of (4.54 ± 0.10) mA cm-2, open circuit voltage (Voc) of (0.51 ± 0.01) V and fill factor (FF) of (0.34 ± 0.03). The QDSSC photoanode is then deposited with ZnS and SiO2 passivation layers and to form the QDSSC with configuration: [FTO / TiO2 / CdS(5) / ZnS / SiO2 / electrolyte / Pt(CE) / FTO]. A PCE of (1.34 ± 0.13)%, Jsc of (7.09 ± 0.27) mA cm-2, Voc of (0.56 ± 0.04) V and FF of (0.34 ± 0.01) have been obtained. Finally, the work investigates the better material for use as CE. Two materials other than Pt have been used as CE i.e. gold (Au) and lead sulphide (PbS). QDSSC fabricated with PbS CE [FTO / TiO2 / CdS(5) / ZnS / SiO2 / electrolyte / PbS(CE) /FTO] shows the best performance with PCE of (2.83 ± 0.07)%, Jsc of (9.54 ± 0.16) mA cm-2, Voc of (0.60 ± 0.02) V and FF of (0.49 ± 0.03).